MOBILE BANKING IN BANGLADESH: A POLICY AND REGULATORY REVIEW - Kabir, Mohammad Rezaul; Hossain, Md. Amzad (Asian Finance & Banking Review, 2023)
Policy and regulatory issues are indispensable for maintaining discipline and protecting the interests of all stakeholders in the mobile banking ecosystem. Bangladesh Bank has issued mobile banking policy guidelines (2011) and mobile financial services regulation (2018) to protect against abuse of these services like financial fraud, money laundering, and terrorist financing, as well as safeguard user funds. This article examined the role of mobile banking policy and the regulatory framework in creating a favourable regulatory environment for mobile banking in Bangladesh. For this purpose, twenty-three KIIs and one questionnaire survey were conducted on 400 respondents in the country's four districts. Many public and private documents and journal articles were also reviewed. A regulatory policy index for mobile banking with ten indicators was developed, and the overall regulatory index score was 0.85 out of 1. Multiple linear regression analysis has also been used in this study. Its regulatory index value, beta coefficient, and R-value, as well as expert opinions, asserted that mobile banking regulatory policy standards have positively influenced the creation of a favourable regulatory environment, even though they demand some modification in terms of account opening minimum age, service charge rate, product diversification, interoperability, and supervision of mobile banking activities. Since multiple agencies are involved in mobile banking policy and regulation, the government can play a vital role in coordination among the multiple agencies to ensure the protection of customers and financial steadiness through a suitable legal structure.JEL Classification Codes: G21, G28, C83.